Friction material composition, brake pad, preparation method of brake pad, brake disc and vehicle

By combining modified silicon-based polymer with cyanite and combining ceramic fibers and carbon fibers and other materials, the problem of poor high-temperature resistance at high temperatures is solved, and higher high-temperature resistance and thermal decay resistance are achieved.

CN119684018APending Publication Date: 2025-03-25BYD CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311242889.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-22
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The phenolic resin used in traditional automotive friction materials has poor high temperature resistance under high temperature conditions, resulting in serious thermal decline.

Method used

The silicon-based polymer is modified by cyanite, and combined with ceramic fibers, carbon fibers, lubricants, abrasive enhancers and fillers to form a new friction material composition. The composition is prepared into brake pads by hot pressing and sintering processes, which improves the high temperature resistance and heat fading resistance of the friction material.

Benefits of technology

It significantly improves the high temperature resistance and heat fading resistance of friction materials, ensuring stable performance and service life under high temperature conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention provides a friction part composition, a brake pad, a preparation method of the brake pad, a brake disc and a vehicle, and the friction part composition comprises 5-25% of modified silicon-based polymer, 10-30% of ceramic fiber, 3-15% of carbon fiber, 10-30% of lubricant, 5-15% of friction increasing agent and 10-55% of filler on the basis of the total mass of the friction part composition. The silicon-based polymer is modified by introducing kyanite, so that the temperature resistance is improved; and the friction piece composition is free of metal components, low in noise and good in heat fading resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of friction materials, and in particular to a friction material composition, a brake pad and a preparation method thereof, a brake disc and a vehicle. Background Art

[0002] Friction materials are usually composed of binders, reinforcing fibers, lubricants, wear enhancers, fillers, etc. Traditional automotive friction materials usually use phenolic resin as a binder, but phenolic resin has poor high temperature resistance and suffers from severe thermal decay in high temperature conditions. Summary of the invention

[0003] In view of this, the present application provides a friction material composition, a brake pad and a preparation method thereof, a brake disc and a vehicle. The friction material prepared from the friction material composition has excellent high temperature resistance and thermal decay resistance.

[0004] In the first aspect, the present application provides a friction material composition, which, based on the total mass of the friction material composition, includes 5-25% of a modified silicon-based polymer, 13-45% of reinforcing fibers, 10-30% of a lubricant, 5-15% of a wear enhancer, and 10-55% of a filler; the modified silicon-based polymer is obtained by modifying a silicon-based polymer with kyanite.

[0005] Optionally, based on the total mass of the friction material composition, the friction material composition includes 12-18% of modified silicon-based polymer, 13-30% of reinforcing fiber, 15-25% of lubricant, 5-8% of wear enhancer, and 20-45% of filler.

[0006] Optionally, based on the total mass of the friction material composition, the friction material composition consists of 12-18% of modified silicon-based polymer, 13-30% of reinforcing fiber, 15-25% of lubricant, 5-8% of wear enhancer, and 20-45% of filler.

[0007] Optionally, in the modified silicon-based polymer, the weight ratio of the kyanite to the silicon-based polymer is 1:(1-5), and more preferably 1:(1.5-2.5).

[0008] Optionally, the silicon-based polymer includes one or more of polysiloxane, polysilazane, polyborosilazane, polycarbosilane, polyborosilane, polyborosiloxane, polyborosilane and polyzirconocarbosilane, and more preferably polysiloxane.

[0009] Optionally, the reinforcing fibers include ceramic fibers and carbon fibers; based on the total mass of the friction material composition, the friction material composition includes 10-30% of ceramic fibers and 3-15% of carbon fibers.

[0010] Optionally, the lubricant includes a carbon material and a metal sulfide, the carbon material includes graphite with a particle size of 80-200 meshes; the metal sulfide includes molybdenum disulfide with a particle size of 100-300 meshes.

[0011] Optionally, the grinding enhancer includes one or more of aluminum oxide, zirconium oxide and magnesium oxide, and the particle size is 100-800 meshes.

[0012] Optionally, the filler includes one or more of barium sulfate, mica, vermiculite, potassium titanate and zirconium silicate, the particle size of the barium sulfate is 300-1250 mesh, and the particle sizes of the mica, vermiculite, potassium titanate and zirconium silicate are each independently 50-300 mesh.

[0013] In a second aspect, the present application provides a brake pad, which is prepared from the friction material composition provided in the first aspect of the present application.

[0014] In a third aspect, the present application provides a method for preparing a brake pad, which comprises the following steps: S1, modifying a silicon-based polymer with kyanite; S2, mixing the friction material composition as described above; S3, hot pressing the mixture after the mixing treatment in S2 to form a blank; S4, sintering the blank after the hot pressing treatment in S3 to obtain the brake pad.

[0015] Optionally, in step S1, an organic solvent is added to the silicon-based polymer and kyanite, the organic solvent includes one or more of ethyl acetate, ethanol, n-hexane, dichloromethane and acetone, the weight ratio of the modified silicon-based polymer to the organic solvent is (5-15):1, and the mixture is mixed into a slurry, and the viscosity of the slurry after mixing is 15-30 Pa·s.

[0016] Optionally, in step S3, the conditions for the hot pressing treatment include a hot pressing pressure of 200-300 kg·f / cm 2 , the hot pressing temperature is 130-150℃.

[0017] Optionally, in step S4, the sintering temperature is 800-1300° C., the sintering pressure is 1-3 MPa, and the sintering time is 1-3 hours.

[0018] In a fourth aspect, the present application provides a brake disc, which includes the friction material composition provided in the first aspect of the present application and / or the brake pad provided in the second aspect.

[0019] In a fifth aspect, the present application provides a vehicle, comprising the brake disc provided in the fourth aspect of the present application.

[0020] Through the above technical scheme, the friction material composition of the present application adopts kyanite-modified silicon-based polymer as a binder, and kyanite can compensate for the volume shrinkage of the silicon-based polymer during the ceramicization process; and then ceramic fiber and carbon fiber are used as the skeleton, assisted by the synergistic effect of lubricants, wear enhancers and fillers, thereby improving the high temperature resistance of the friction material prepared by the friction material composition, and the strength is higher.

[0021] Other features and advantages of the present application will be described in detail in the subsequent detailed description. DETAILED DESCRIPTION

[0022] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0023] The present application provides a friction material composition for a friction part, which comprises, based on the total mass of the friction material composition for a friction part, 5-25% of a modified silicon-based polymer, 13-45% of a reinforcing fiber, 10-30% of a lubricant, 5-15% of a wear enhancer, and 10-55% of a filler; The modified silicon-based polymer is obtained by modifying a silicon-based polymer with kyanite. The crystal form of kyanite (Al2SiO4) changes at high temperature and transforms into mullite (2Al2O3·SiO2). The reaction is accompanied by obvious volume expansion, which can compensate for the volume shrinkage of the silicon-based polymer during the ceramicization process.

[0024] The components of the friction material composition include modified silicon-based polymer, ceramic fiber, carbon fiber, lubricant, wear enhancer and filler. The modified silicon-based polymer can be transformed into a bonding phase containing Si-OC, Si-C, and Si-N after high-temperature treatment, and plays the role of a binder; the ceramic fiber and carbon fiber serve as a skeleton to support the overall structure; the lubricant and wear enhancer adjust the friction performance; and the filler plays an auxiliary filling role. In the present application, the components in the friction material composition work synergistically to obtain a friction material with strong high temperature resistance and good friction performance.

[0025] In one embodiment of the present application, the mass content of the modified silicon-based polymer in the friction material composition is 5-25%, and more preferably 12-18%, which is conducive to the regulation of the bonding effect of the friction material composition. Specifically, the mass content of the modified silicon-based polymer in the friction material composition can be, but is not limited to, 5%, 6%, 9%, 12%, 15%, 18%, 21%, 24% or 25%. In the present application, the modified silicon-based polymer is formed by modifying the silicon-based polymer with kyanite. The silicon-based polymer undergoes a ceramicization process when treated at high temperature. Since the organic matter containing CH and CO groups inside decomposes at high temperature, pores and voids are easily generated inside. The crystal form of the kyanite changes at high temperature and turns into mullite. The reaction is accompanied by obvious volume expansion, which can play a filling role and compensate for the volume shrinkage of the silicon-based polymer during the ceramicization process.

[0026] In one embodiment of the present application, the silicon-based polymer includes one or more of polysiloxane, polysilazane, polyborosilazane, polycarbosilane, polyborosilane, polyborosiloxane, polyborosilane and polyzirconocarbosilane, preferably polysiloxane. Polysiloxane is cheap and easy to obtain, and has higher strength after ceramicization. In one embodiment of the present application, the weight ratio of kyanite to the content of the silicon-based polymer is 1: (1-5), preferably 1: (1.5-2.5). By controlling the weight ratio of kyanite to the silicon-based polymer within this range, the pores generated during the high-temperature ceramicization of the silicon-based polymer can be further matched when the kyanite expands at high temperature.

[0027] In one embodiment of the present application, the mass content of the reinforcing fiber in the friction material composition is 13-45%, and more preferably 13-30%. The reinforcing fiber includes ceramic fiber and carbon fiber. In one embodiment of the present application, the mass content of the ceramic fiber in the friction material composition is 10-30%, and more preferably 10-20%, which is conducive to the regulation of the strength of the friction material composition. In one embodiment of the present application, the mass content of the carbon fiber in the friction material composition is 3-15%, and more preferably 3-12%, which is conducive to the regulation of the toughness of the friction material composition.

[0028] In one embodiment of the present application, the mass content of the lubricant in the friction material composition may be 10-30%, and more preferably 15-25%, and plays a lubricating role in the friction material composition.

[0029] In one embodiment of the present application, the lubricant includes a carbon material and a metal sulfide, wherein the carbon material includes graphite with a particle size of 80-200 meshes, and the friction material composition composed of graphite with a particle size within this range is easy to form a friction surface when performing a friction performance test, and has good friction performance; the metal sulfide includes molybdenum disulfide with a particle size of 100-300 meshes, and the friction material composition composed of molybdenum disulfide with a particle size within this range is easy to form a friction surface when performing a friction performance test, and has good friction performance. In one embodiment of the present application, the lubricant includes flake graphite and molybdenum disulfide. Graphite can provide a good lubrication effect at medium and low temperatures, while metal sulfides can not only provide a lubrication effect at medium and low temperatures, but also metal oxides formed by high-temperature oxidation also have a certain lubrication effect and stabilize the friction coefficient.

[0030] In one embodiment of the present application, the mass content of the wear-increasing agent in the friction material composition can be 5-15%, more preferably 5-8%, and plays a role in increasing the friction coefficient in the friction material composition. In one embodiment of the present application, the wear-increasing agent includes one or more of aluminum oxide, zirconium oxide and magnesium oxide. In one example of the present application, the wear-increasing agent includes zirconium oxide.

[0031] In one embodiment of the present application, the mass content of the filler in the friction material composition can be 10-55%, and more preferably 20-45%. In the friction material composition, the filler plays a role in reducing the shrinkage of the pressed composition, and can improve the dimensional stability, surface finish and smoothness of the product. In one embodiment of the present application, the filler includes one or more of barium sulfate, mica, vermiculite, potassium titanate and zirconium silicate. The particle size of the barium sulfate is 300-1250 mesh, and the particle size of the mica, vermiculite, potassium titanate and zirconium silicate is 50-300 mesh. The filler within the above particle size range is easier to press and mold during pressing, and it is easy to obtain a densified brake pad product. In one embodiment of the present application, the filler includes barium sulfate, mica, vermiculite and potassium titanate whiskers.

[0032] In one embodiment of the present application, based on the total mass of the friction material composition, the friction material composition of the friction part is composed of 12-18% of modified silicon-based polymer, 13-30% of reinforcing fiber, 15-25% of lubricant, and 5-8% of wear enhancer. The friction material composition does not contain metal components and resins, but is a full ceramic-based component, and the content of each component is appropriate. The friction material prepared is environmentally friendly, low in noise, good in heat decay resistance and high temperature resistance, and has no risk of rust.

[0033] The present application provides a brake pad, comprising the friction material composition in any of the above embodiments. The brake pad made of the above friction material composition has good high temperature resistance and good thermal decay resistance, and can improve the performance of the brake pad under high temperature conditions.

[0034] The present application provides a method for preparing a brake pad, which can be used to prepare a brake pad comprising the friction material composition of any of the above-mentioned embodiments, comprising: S1, modifying a silicon-based polymer with kyanite; S2, mixing the friction material composition as described above; S3, hot pressing the mixture after the mixing treatment in S2 to form a blank; S4, sintering the blank after the hot pressing treatment in S3 in an inert atmosphere to obtain the brake pad.

[0035] In the present application, the components for preparing the friction material composition are mixed, hot pressed, sintered, and then processed to obtain the brake pad; the preparation method is simple, and the brake pad prepared by this method has good high temperature resistance and good thermal decay resistance.

[0036] In step S1, an organic solvent is added to the silicon-based polymer and kyanite, and the organic solvent includes one or more of ethyl acetate, ethanol, n-hexane, dichloromethane and acetone, which is used to wet-mix the silicon-based polymer and kyanite so that the two are better mixed and have a suitable viscosity, and are convenient for subsequent mixing with other components to ensure that the silicon-based polymer and kyanite are uniformly dispersed in the total material. The purity of the organic solvent can be analytically pure, and the mass ratio of the modified silicon-based polymer to the organic solvent can be (5-15): 1. In one embodiment of the present application, the organic solvent used can be ethanol. In one embodiment of the present application, the ratio of the modified silicon-based polymer to the organic solvent can be (8-12): 1. In one embodiment of the present application, the viscosity of the slurry after the modified silicon-based polymer and the organic solvent are mixed can be 15-30Pa·s, which is conducive to the subsequent better mixing of the modified silicon-based polymer with other components and playing a bonding role. Specifically, the viscosity of the mixed slurry may be, but is not limited to, 15 Pa·s, 18 Pa·s, 20 Pa·s, 21 Pa·s, 25 Pa·s or 30 Pa·s, etc.

[0037] In one embodiment of the present application, the kyanite-modified silicon-based polymer is mixed with ceramic fiber, carbon fiber, lubricant, grinding agent and filler. Specifically, they can be put into a mixer for mixing until they are evenly mixed.

[0038] In step S3, the mixture after the treatment in step S2 is subjected to hot pressing. In one embodiment of the present application, the hot pressing pressure may be 200-300 kg·f / cm 2, the hot pressing temperature can be 130-150°C, and the mixture is pressed into a blank. Furthermore, since the aforementioned mixing process uses a wet mixing method, the mixture contains an organic solvent, which is volatile at high temperatures, and cracks are easily generated when the mixture is pressed without exhaust. In order to prevent the generation of cracks, exhaust operation is required, and exhaust is performed once every 10-15s of pressing, for a total of 7-10 times, and the total heat preservation is 10-15min. In one embodiment of the present application, the blank after S3 hot pressing treatment is sintered in an inert atmosphere. Specifically, the blank can be placed at 800-1300°C and a pressure of 1-3MPa, and kept in a vacuum or inert atmosphere, such as argon, helium, etc. for 1-3 hours to be fired into a brake pad.

[0039] The present application provides a brake disc, comprising the friction material composition and / or brake pad in any of the above embodiments or a brake pad prepared by the preparation method in any of the above embodiments.

[0040] The present application provides a vehicle, comprising a brake disc in any one of the above-mentioned embodiments.

[0041] The effect of the technical solution of this application is further illustrated below through specific examples.

[0042] Example 1 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 15% (wherein the weight ratio of kyanite to polysiloxane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 15%.

[0043] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 20 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0044] Example 2 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 24% (wherein the weight ratio of kyanite to polysiloxane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 6%.

[0045] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 30 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0046] Example 3 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 6% (wherein the weight ratio of kyanite to polysiloxane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 24%.

[0047] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 15 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0048] Example 4 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 15% (wherein the weight ratio of kyanite to polysiloxane is 1:1), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 15%.

[0049] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 25 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank. The hot press pressure is 15% and the pressure is 300kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0050] Example 5 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 15% (wherein the weight ratio of kyanite to polysiloxane is 1:5), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 15%.

[0051] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 18 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0052] Example 6 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysilazane 15% (wherein the weight ratio of kyanite to polysilazane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 15%.

[0053] The preparation of brake pads includes the following steps: 1) Add ethanol to polysilazane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 21 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0054] Example 7 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polyborosilane 15% (wherein the weight ratio of kyanite to polyborosilane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 15%.

[0055] The preparation of brake pads includes the following steps: 1) Add ethanol to polyborosilane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 18 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0056] Example 8 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane and polyborosilane 15% (wherein the weight ratio of kyanite to polysiloxane and polyborosilane is 1:1:1), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 15%.

[0057] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane, polyborosilane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 20 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0058] Example 9 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 15% (wherein the weight ratio of kyanite to polysiloxane is 1:2), carbon fiber 7%, potassium hexatitanate whisker 5%, alumina fiber 23%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 15%.

[0059] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 20 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0060] Example 10 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 15% (wherein the weight ratio of kyanite to polysiloxane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 5%, flake graphite 15%, zirconium oxide 5%, and barium sulfate 15%.

[0061] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 20 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0062] Embodiment 11 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 15% (wherein the weight ratio of kyanite to polysiloxane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 10%, alumina fiber 25%, mica 3%, vermiculite 2%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, and barium sulfate 15%.

[0063] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 20 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0064] Example 12 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 15% (wherein the weight ratio of kyanite to polysiloxane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 3%, vermiculite 2%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 10%, and barium sulfate 15%.

[0065] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 20 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0066] Comparative Example 1 The weight percentages of the components of the friction material composition of this embodiment are as follows: Polysiloxane 15%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, barium sulfate 15%.

[0067] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 16 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0068] Comparative Example 2 The weight percentages of the components of the friction material composition of this embodiment are as follows: Phenolic resin 15%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, zirconium oxide 5%, barium sulfate 15%.

[0069] The preparation of brake pads includes the following steps: 1) The above raw materials are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials are evenly distributed; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 , hot pressing temperature is 150℃, exhaust once every 10s, exhaust 10 times in total, and keep warm for 15min in total; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0070] Comparative Example 3 The weight percentages of the components of the friction material composition of this embodiment are as follows: Kyanite modified polysiloxane 30% (wherein the weight ratio of kyanite to polysiloxane is 1:2), carbon fiber 5%, potassium hexatitanate whisker 5%, alumina fiber 25%, mica 6%, vermiculite 4%, molybdenum disulfide 15%, flake graphite 5%, and barium sulfate 5%.

[0071] The preparation of brake pads includes the following steps: 1) Add ethanol to polysiloxane and kyanite, and mix them into slurry by ball milling. The viscosity of the slurry after mixing is 20 Pa·s; 2) The slurry and the raw materials of each component are fully mixed in a plowshare mixer for 15 minutes to obtain a mixture in which the raw materials of each component are evenly distributed; 3) The above mixture is fed into an automatic hot press and pressed into a blank at a hot press pressure of 300 kg·f / cm 2 The hot pressing temperature is 150℃, the air is exhausted every 10 seconds, a total of 10 times, and the heat preservation is 15 minutes; 4) The blank is sent into a vacuum furnace and sintered in an inert atmosphere at a sintering temperature of 1000°C for 2 hours; 5) According to the brake pad specifications or test requirements, the sintered green body is processed to obtain the brake pad.

[0072] Performance Testing (1) Constant speed friction and wear test The brake pads prepared in the above embodiments and comparative examples were subjected to constant speed friction and wear tests according to the relevant test standards specified in GB 5763-2008. The friction coefficient, wear rate and bending strength of the brake pads were tested at braking temperatures of 100°C, 200°C, 300°C and 350°C, respectively. The test results are shown in Table 1.

[0073] (2) Rotational friction performance test The brake pads prepared in the above-mentioned embodiments and comparative examples were tested for rotational friction performance at 1000° C. on a MFT-5000 friction and wear testing machine. The test results are shown in Table 2.

[0074] Table 1 Test results of friction coefficient, wear rate and bending strength at different braking temperatures

[0075] Table 2 Rotational friction performance test results

[0076] As can be seen from Table 1, the brake pad provided by the present application has a stable friction coefficient, a low wear rate and a high bending strength. However, the bending strength of the comparative example 1 without adding kyanite is low and the wear rate is also high. The wear rate of the comparative example 2 using phenolic resin is also high under high temperature conditions.

[0077] As shown in Table 2, the average friction coefficient of each embodiment at 1000°C is higher than that at medium and low temperatures, and no thermal decay occurs. However, the wear rate of Comparative Example 1 without adding kyanite and Comparative Example 2 using phenolic resin is higher under high temperature conditions.

[0078] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A friction material composition, characterized in that: Based on the total mass of the friction material composition, the friction material composition includes 5-25% of modified silicon-based polymer, 13-45% of reinforcing fiber, 10-30% of lubricant, 5-15% of wear enhancer, and 10-55% of filler; the modified silicon-based polymer is obtained by modifying the silicon-based polymer with kyanite.

2. The friction material composition according to claim 1, characterized in that: Based on the total mass of the friction material composition, the friction material composition includes 12-18% of modified silicon-based polymer, 13-30% of reinforcing fiber, 15-25% of lubricant, 5-8% of wear enhancer, and 20-45% of filler.

3. The friction material composition according to claim 1, characterized in that: Based on the total mass of the friction material composition, the friction material composition consists of 12-18% of modified silicon-based polymer, 13-30% of reinforcing fiber, 15-25% of lubricant, 5-8% of wear enhancer, and 20-45% of filler.

4. The friction material composition according to claim 1, characterized in that: In the modified silicon-based polymer, the weight ratio of the kyanite to the silicon-based polymer is 1:(1-5).

5. The friction material composition according to claim 1, characterized in that: The silicon-based polymer includes one or more of polysiloxane, polysilazane, polyborosilazane, polycarbosilane, polyborosilane, polyborosiloxane, polyborosilane and polyzirconocarbosilane.

6. The friction material composition according to claim 5, characterized in that: The silicon-based polymer includes polysiloxane.

7. The friction material composition according to claim 1, characterized in that: The reinforcing fibers include ceramic fibers and carbon fibers; based on the total mass of the friction material composition, the friction material composition includes 10-30% of ceramic fibers and 3-15% of carbon fibers.

8. The friction material composition according to claim 1, characterized in that: The lubricant includes a carbon material and a metal sulfide, wherein the carbon material includes graphite; and the metal sulfide includes molybdenum disulfide.

9. The friction material composition according to claim 1, characterized in that: The wear enhancing agent includes one or more of aluminum oxide, zirconium oxide and magnesium oxide.

10. The friction material composition according to claim 1, characterized in that: The filler includes one or more of barium sulfate, mica, vermiculite, potassium titanate and zirconium silicate.

11. A brake pad, characterized in that: The friction material is prepared from the friction material composition according to any one of claims 1 to 10.

12. A method for preparing a brake pad, characterized in that: The method comprises the following steps: S1, modifying a silicon-based polymer with kyanite; S2, mixing the friction material composition as described in any one of claims 1 to 8; S3, hot pressing the mixture after the mixing treatment in S2 to form a blank; S4, sintering the blank after the hot pressing treatment in S3 to obtain the brake pad.

13. The method for preparing a brake pad according to claim 12, characterized in that: In the step S1, an organic solvent is added to the silicon-based polymer and kyanite, and the organic solvent includes one or more of ethyl acetate, ethanol, n-hexane, dichloromethane and acetone, and mixed into a slurry, and the viscosity of the slurry is 15-30 Pa·s.

14. The method for preparing a brake pad according to claim 12, characterized in that: In step S3, the hot pressing pressure is 200-300 kg·f / cm 2 , the hot pressing temperature is 130-150℃.

15. The method for preparing a brake pad according to claim 12, characterized in that: In the step S4, the sintering temperature is 800-1300° C., the sintering pressure is 1-3 MPa, and the sintering time is 1-3 hours.

16. A brake disc, characterized in that: The brake disc comprises the brake pad according to claim 11 or a brake pad prepared by any one of the methods of claims 12-15.

17. A vehicle, characterized in that: The vehicle comprises the brake disc of claim 16.